Pengaruh Kesadaran Keluarga dan Perencanaan Keuangan Terhadap Investasi Pendidikan Anak - Emilia Tasmal; Iman Fauzi Sudirman; Rosid Bahar (Jurnal Ilmiah Ekonomi dan Manajemen Indonesia, 2026)
This research is motivated by the problem of the continuously increasing cost of education in Indonesia, which has become an obstacle for many students, including those within the Idrisiyyah Islamic Boarding School environment. The increase in education costs at various levels, from elementary school to higher education, is not always aligned with an increase in the quality of education. This highlights the importance of family awareness in preparing for children's education investment through effective financial planning. Although awareness and financial planning are recognized as crucial factors, many families have not yet realized their importance. This study aims to analyze the influence of family awareness and financial planning on children's education investment, particularly among the Jamaah Idrisiyyah in Zawiyah, Tasikmalaya Regency, to support children's educational success and the achievement of quality educational goals. This research aims to analyze the influence of family awareness and financial planning on children's education investment. Specifically, this research aims to: (1) determine the influence of family awareness on children's education investment, (2) determine the influence of financial planning on children's education investment, and (3) determine the combined influence of family awareness and financial planning on children's education investment. This research uses a quantitative approach to analyze the influence of family awareness and financial planning on children's education investment. Data were collected from 170 Family Cards of Jamaah Idrisiyyah in Tasikmalaya Regency through questionnaires distributed using Google Forms. The sampling technique used is simple random sampling. The research instrument uses the Likert scale, and data were analyzed using validity tests, reliability tests, multiple linear regression, and classical assumption tests (normality, multicollinearity, and heteroscedasticity) using SPSS. This research shows that family awareness and financial planning have a significant influence on children's education investment among the Jamaah Idrisiyyah in Tasikmalaya Regency. Family awareness and financial planning together explain 73% of the variation in children's education investment.